An Analysis of Tracheostomy Complications in Pediatric Patients With Scoliosis. (27th July 2021) - Appachi, Swathi; Marcet‐Gonzalez, Jessie; Brown, Jennifer N.; Ongkasuwan, Julina; Lambert, Elton M.
Abstract : Objectives/Hypothesis: To analyze tracheostomy‐related complications in pediatric patients with scoliosis. Study Design: Retrospective chart review. Methods: A retrospective chart review of all patients with tracheostomy and scoliosis was performed at a single institution. The charts were reviewed for variables including difficulties with tracheostomy tube changes, poor positioning of tube, abnormal appearance of trachea, and emergency room visits and admissions for complications. Decannulation rates were also identified. Results: About 102 patients met inclusion criteria, 96 (94.1%) had scoliosis involving the thoracic spine, and 4 had scoliosis involving the cervical spine; 13 (12.8%) patients had documented poor positioning on tracheoscopy; 31 patients (30.3%) had at least one emergency room visit or admission for complications, such as accidental decannulation or bleeding from the tracheostomy; 19 (18.6%) patients required at least one tube change due to poor positioning, with 7 (6.9%) requiring multiple changes; 18 (17.7%) had reported difficulties with home tube changes. Custom length tubes were required in 9 patients (8.8%). The level of scoliosis was not associated with any of these complications. Abnormalities of the trachea, such as tortuosity, obstructive granulomas, or tracheomalacia, were seen in 35 patients (34.3%) on bronchoscopy. Scoliosis repair was performed in 18 patients (17.65%), of which two achieved decannulation. Ten patients (9.8%) overall were decannulated. Conclusion: A portion of patients with scoliosis who are tracheostomy‐dependent have anatomical abnormalities of the trachea and poor positioning of the tracheostomy tube. Decannulation rates are also lower in this population compared to the literature. Further work is required to elucidate if scoliosis predisposes patients toward tracheostomy‐related complications. Level of Evidence: 4 Laryngoscope, 132:944–948, 2022